R290 (propane) and R600a (isobutane) as natural refrigerants for residential heat pump water heaters. (25th December 2017) - Nawaz, Kashif; Shen, Bo; Elatar, Ahmed; Baxter, Van; Abdelaziz, Omar
Highlights: A HPDM model has been used to evaluate the performance of hydrocarbon as refrigerants for HPWH applications. The UEF and FHR have been used to evaluate the performance of R134a, R290 and R600a refrigerants. Different condenser wrap patterns and storage tank thermal insulation effectiveness have been consider. The impact of compressor discharge temperature, water stratification has been evaluated. The impact of saturation temperature change in condenser and total refrigerant charge has been evaluated. Abstract: Growing awareness of the potential environmental impacts of various refrigerants has led to the phasedown of hydrofluorocarbon (HFC) refrigerants and to initiatives replacing HFCs with hydrocarbons or other environmentally friendlier fluids. This study evaluated the performance of R290 (propane) and R600a (isobutane) as substitutes for R134a (a HFC) for heat pump water heating (HPWH). A component-based model (calibrated against the experimental data) was used to predict the performance of the HPWH system. Key performance parameters such as unified energy factor, first hour rating, condenser discharge temperature, thermal stratification in the water tank, and total refrigerant charge were investigated. Analysis results suggest that both alternative refrigerants could provide comparable system performance to that of the baseline system containing R134a, with one caveat. As a drop-in alternative, R290 was found to be a better substitute for R134a, whereas R600a is expected to provide similar performance if the compressor size is increased to provide similar heating capacity. Significant reductions in system charge and lower condenser discharge temperatures were identified as additional benefits.